Environmental design of low-head run-of-river hydropower in the United States: A review of facility design models. (May 2022) - Sasthav, Colin; Oladosu, Gbadebo
Abstract: The goal of run-of-river hydropower is to produce cost-competitive renewable electricity with minimal disruption of the natural riverine ecosystem. Modeling and feasibility analysis of alternative design options are crucial for developing new run-of-river hydropower projects. Our review shows that existing run-of-river hydropower design models focus on maximizing economic potential at high-head diversion schemes with limited consideration of environmental outcomes. Since nearly three-quarters of new hydropower potential in the United States is found at low-head sites and environmental performance standards are imperative to project success, new models are needed to address the multi-dimensional design challenges at these sites. To aid in formulating holistic models, we synthesize the performance objectives and design variables related to early-stage run-of-river facility design. The objectives span six potential impact areas, including hydrologic alteration, sediment continuity, water quality, aquatic species passage, social, and economic. Based on these reviews, we identify three key areas to enhance the capabilities of run-of-river hydropower design models. These are 1) expanded model formulations, 2) assessment of barrier effects, and 3) explicit environmental objectives. The resulting modeling improvements would accelerate the identification of run-of-river hydropower designs that minimize environmental impacts, promote economic competitiveness, and incorporate the value of non-power benefits. Highlights: Current hydropower design models focus on economic potential of high-head projects. New hydropower plants in the US will likely be low-head, instream, and run-of-river. Flow allocation, technology selection, and headpond design are critical decisions. Barrier effects on fish, sediment, and recreation should be modeled. Win-win designs are possible when non-power benefits are explicitly optimized.